Rep1 copy number variation is an important genetic cause of choroideremia in Chinese patients. (November 2017) - Zhou, Qi; Yao, Fengxia; Han, Xiaoxu; Li, Hui; Yang, Lizhu; Sui, Ruifang
Abstract: Choroidermia (CHM) is an X-linked chorioretinal disorder caused by mutations in the Rab Escort Protein 1 ( Rep-1 ) gene. Its diagnosis depends on clinical findings and genetic confirmation; however, mutations in Rep-1 gene are not always detected by standard Sanger sequencing. We therefore conducted multiplex ligation-dependent probe amplification (MLPA) and real-time quantitative PCR (QPCR) in cases of Chinese CHM families in which sequencing all the exons and flanking intronic regions of the CHM gene had not identified a mutation or exons could not be amplified. We hypothesized that copy number variation (CNV) within the Rep-1 gene would explain the etiology of choroideremia in these patients. In the eight unrelated families, exon deletions or duplications were detected by MLPA and QPCR in five. Our results showed CNV within the Rep-1 gene could be an important contributor in Chinese CHM patients. Sequencing of the Rep-1 gene supplemented with MLPA is therefore an important diagnostic strategy in choroideremia patients. Highlights: Standard Sanger sequences cannot detect Rep-1 mutations in 22% Chinese CHM families (7 out of 32). MLPA detected exon deletions or duplications in 5 those families. CNV is an important genetic cause in Chinese CHM patients. MLPA should be performed if Sanger sequences failed to detect Rep-1 mutations in clinical diagnosed CHM patients.